Based on Fermentation Technology, Compost Waste Processing uses Effective Microorganisms to Manufacture Organic Fertilisers - Rappi Ahmad Ajini (Akademi Sertifikasi Profesi Internasional, 2023)
Aims to teach and prepare farming communities to use natural resources, particularly household vegetable and fruit waste that hasn't been used effectively, by applying fermentation technology, which is still unfamiliar to many, to turn it into more useful and eco-friendly products using effective microorganisms. So far, the community has not gotten any intense attention or understanding about discovering alternate solutions that can be applied to trash, notably domestic organic waste. Bokashi fertiliser is an organic fertiliser created from the fermentation of organic resources, such as compost, and utilises microorganisms like bacteria or fermenting fungus. The outcome is a solid fertiliser that includes more nutrients, both macro and micro, which are ready to be taken by plant roots. The purpose of the fertiliser activity is to provide training and build community skills in processing organic materials from home garbage. The programme also seeks to introduce the community to fermentation technology for the disposal of organic waste. The effort empowers the community, particularly farmers, to cultivate an inventive mentality in solving environmental concerns, which covers activities such as mentoring, group involvement, and innovation. The results of this analysis have a favourable impact on the knowledge and abilities of the farming community regarding the use of domestic organic waste. The findings of the evaluation of the questionnaire suggested that participants felt the benefits of the activity, exhibited curiosity, received new knowledge, and were willing to implement it in their daily life